Evaluation of influenza-specific immunoglobulin Y stability in liquid, solid, and cream-based body care formulations - Poetri, Okti Nadia; Setyawati, Yusefin Marcelina; Kal Alfin, Zabrino Wahid; Kalsum, Salsabila; Fathurrahman, Fathurrahman; Rong, Chin Xiao; Nugraheni, Indi Amalia; Kuswanti, Andrea Septiandra (Current Biomedicine, 2025)
Background Specific immunoglobulin Y (IgY) is widely used in immunotherapy, with expanding applications in body care products. Topically applied influenza-specific antibodies may provide an alternative strategy for preventing respiratory infections. Objective This study aimed to evaluate the stability and biological activity of influenza-specific IgY in various body care products. Methods The biological activity of influenza-specific IgY was evaluated in various body care products at different concentrations. Commercial face mists contained 5% and 10% w/v IgY, face mists and nasal sprays contained 0.5% w/v IgY, lip balm, sunscreen, and hand cream contained 0.1% and 0.25% w/v IgY. The products were stored at room temperature for four weeks, and organoleptic changes were monitored weekly. IgY activity was assessed by enzyme-linked-immunosorbent-assay (ELISA). Results In both face mist products, the aroma gradually became fishy, the color remained stable, and turbidity increased. The biological activity of IgY was still detectable by ELISA at concentrations of 0.5%, 5%, and 10%. In nasal spray, no changes in aroma, color, or turbidity were observed, but IgY activity was not detectable. In lip balm, sunscreen, and hand cream, only slight color changes occurred without any change in aroma, and IgY activity was not detected. Conclusion Influenza-specific IgY retained biological activity in face mist formulations at higher concentrations (≥0.5%) despite observable changes in aroma and turbidity. In contrast, IgY activity was not detected in nasal sprays, lip balm, sunscreen, or hand cream, suggesting that the formulation type and IgY concentration significantly influence its stability and detectability in body-care products.